2013
DOI: 10.1002/path.4226
|View full text |Cite
|
Sign up to set email alerts
|

The paracrine effect of cancer-associated fibroblast-induced interleukin-33 regulates the invasiveness of head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the leading causes of cancer-related death worldwide. The prognosis of HNSCC is usually poor because of its propensity for extensive invasion, local recurrence and frequent regional lymph node metastasis, even at initial diagnosis. Carcinoma-associated fibroblasts (CAFs), a major type of tumour-surrounding stromal cell, generate mediators through which they interact with tumours and contribute to cancer progression. The orchestration between CAFs and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 41 publications
(45 reference statements)
5
104
1
3
Order By: Relevance
“…The prognostic significance of IL-33 was also examined. Several studies have shown that a high expression of IL-33 is associated with a poor prognosis in diverse cancers and may be a potential prognostic factor (23,25,26). However, opposing findings in different types of cancers have also been reported.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…The prognostic significance of IL-33 was also examined. Several studies have shown that a high expression of IL-33 is associated with a poor prognosis in diverse cancers and may be a potential prognostic factor (23,25,26). However, opposing findings in different types of cancers have also been reported.…”
Section: Introductionmentioning
confidence: 86%
“…It has been shown that increased IL-33 expression may influence the survival in certain types of cancer patients (23,25,26,28). Hence, we also analyzed the relationship between IL-33 expression and clinical prognosis in CRC patients.…”
Section: The Predicating Significance Of Il-33 Level In the Adenomas mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 has been reported as a potent inducer of Th2 immune responses as well as "alarmin" cytokine released from necrotic cells (Arshad et al, 2012;Lopetuso et al, 2012;Roy et al, 2014). Recently, some DOI:http://dx.doi.org/10.7314/APJCP.2014.15.8.3503 Correlations Between Serum IL33 and Tumor Development: a Meta-analysis researches reported that IL-33 is play important role in tumorigenesis and tumor progress (Chen et al, 2013;Jovanovic et al, 2014)Serum IL-33 may be a useful indicator for prognosis of tumor (Sun et al, 2011). In here, our meta-analysis included eight papers results shown that IL33 expression level is higher in tumor patients that in healthy people, so, there is a clinical value that IL-33 can be as a potential diagnostic for tumor patient.…”
Section: Discussionmentioning
confidence: 99%
“…We first found 723 studies which met inclusion criteria, after reviewing carefully, all of the eight papers (Sun et al, 2011;Naumnik et al, 2012;Zhang et al, 2012;Bergis et al, 2013;Chen et al, 2013;Gangemi et al, 2013;Hu et al, 2013;Santulli et al, 2013). were included into this meta-analysis.…”
Section: Generally Datamentioning
confidence: 99%